Diversity of New Martian Crater Clusters Informs Meteoroid Atmospheric Interactions - Neidhart, Tanja; Sansom, Ellie; Miljkovic, Katarina; Collins, G.S.; Eschenfelder, J.; Daubar, I.J. (American Geophysical Union, 2023)
We investigated 634 crater clusters on Mars detected between 2007 and 2021, which represent more than half of all impacts discovered in this period. Crater clusters form when meteoroids in the 10 kg–10 ton mass range break up in Mars' atmosphere to produce a few to a few hundred fragments that hit the ground. The properties of the clusters can inform our understanding of meteoroid properties and the processes that govern their fragmentation. We mapped individual craters >1 m within each cluster and defined a range of cluster properties based on the spatial and size distributions of the craters. The large data set, with over eight times more cluster observations than previous work, provides a more robust statistical investigation of crater cluster parameters and their correlations. Trends in size, dispersion, and large crater fraction with elevation support weak atmospheric filtering of material. The diversity in the number of individual craters within a cluster, and their size-frequency distributions, may reflect either a diversity in fragmentation style, fragility, or internal particle sizes.